Health and socio-economic hazards associated with khat consumption - Hussein M. A. Ageely (Wolters Kluwer Medknow Publications, 2008)
The consumption of the stimulant leaf Khat (Catha edulis Forsk) is widespread in several countries of East Africa and the Arabian Peninsula. The leaf comes from a small evergreen shrub that can grow to the size of a tree. Young buds and tender leaves are chewed to attain a state of euphoria and stimulation. Khat leaves contain cathinones, an active brain stimulant that is similar in structure and pharmacological activity to amphetamines. Like amphetamines, Khat ingestion in low doses results in decreased appetite, euphoria, increased intellectual efficiency, and hyperalertness. High doses and chronic use of Khat can cause more serious adverse neurological, psychiatric, cardiovascular, dental, gastrointestinal and genitourinary effects. Besides damaging health, Khat has adverse socio-economic consequences effects on many other aspects of life including the loss of thousands of acres of arable land and billions of hours of work. The purpose of this review is to describe briefly the adverse consequences of habitual chewing of Khat on health, and help educate the general public. The study is based on literature review that includes internet search and journals.